Proof of correctness of ATM retransmission scheme. - Simmons, Jane M. (Computer networks and ISDN systems.)
The ITU has designed a poll based retransmission scheme as part of the Service Specific Connection Oriented Protocol for ATM systems. The basic scheme consists of the transmitter periodically sending polls to the destination indicating which frames have been sent, and the receiver responding with a status message indicating which of these frames have not been received. Many additional features have been included in the scheme in order to reduce the retransmission delay and prevent unnecessary retransmissions. With the added complexity of these features, it is not readily apparent whether the scheme operates correctly. In this paper, it is shown that the scheme does satisfy the properties of liveliness and safety; the source can continue forever to accept frames for transmissions, and all frames are eventually delivered in proper sequence at the destination, assuming that certain conditions hold. In addition, it is shown that unnecessary retransmission do not occur.